2019
DOI: 10.1557/jmr.2018.441
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition (ALD) of subnanometer inorganic layers on natural cotton to enhance oil sorption performance in marine environments

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…This might be caused by the formation of hydrophobic surface after the first few ALD cycles which was due to adventitious carbon absorption arising from the exposure of a few polar Al− O−C bonds on nanofibers, and the hydrophobic surface could prevent water from permeating into aerogels. 22 After absorption saturation, 6cy-ALD aerogel floated on the water, while 0cy-ALD aerogels sank into the water (Figure S9). However, the 7cy-ALD NFAs exhibited comparably less saturation absorption time (120 min) than 6cy-ALD aerogels, but a higher absorption capacity (40.0 g/g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be caused by the formation of hydrophobic surface after the first few ALD cycles which was due to adventitious carbon absorption arising from the exposure of a few polar Al− O−C bonds on nanofibers, and the hydrophobic surface could prevent water from permeating into aerogels. 22 After absorption saturation, 6cy-ALD aerogel floated on the water, while 0cy-ALD aerogels sank into the water (Figure S9). However, the 7cy-ALD NFAs exhibited comparably less saturation absorption time (120 min) than 6cy-ALD aerogels, but a higher absorption capacity (40.0 g/g).…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification is another efficient method to improve asperity, specific surface area, and thermal and mechanical properties as well as the physical and chemical durability of fibrous materials especially at the nanoscale. 21,22 Liquid-phase deposition (LPD) has been demonstrated to be an effective surface modification method. Xiang 23 et al treated the bacterial cellulose aerogels with trimethylchlorosilane in the liquid phase to create a hydrophobic but oleophilic coating at the surface of aerogels.…”
mentioning
confidence: 99%
“…Various porous materials, such as cotton, aerogels, and foams, can be used for regenerable oil sorption by virtue of the significant accessible pore volume and flexible skeleton scaffold for regeneration treatment. 20,[102][103][104] Another critical feature of a sorbent is its selectivity for the targeted substance (in this case, oil), which in turn relates to the surface properties. Interface wettability is collectively determined by surface micro-structure/roughness and surface chemical composition.…”
Section: Oleophilic Sorbentsmentioning
confidence: 99%
“…153 ). 102 This tailored cotton could realize sorption of 23 g/g of crude oil, a 35-fold enhancement compared with the nascent sample (Figure 8A). A key feature of ALD (and SIS) interface modification is often improved mechanical stability of the material modified.…”
Section: Oleophilic Sorbentsmentioning
confidence: 99%
“…Atomic layer deposition (ALD) is known to be a powerful ultrathin film fabrication method based on the time-sequenced self-limiting reactions, and the film thickness and uniformity can be controlled precisely even when applied to the large-area substrates [32]. The densely packed and pinhole-free ALDbased films can be deposited directly on the devices through low-temperature processes, and the conformal films can be utilized as high-quality barriers for organic devices [33,34,35]. In this review, different ALD-based approaches are introduced to solve the specific problems shown in Fig.…”
Section: Introductionmentioning
confidence: 99%